القروض المصغرة كألية مستخدمة لتمويل المشاريع المصغرة للأفراد في الجزائر دراسة حالة الوكالة الوطنية لتسييير القرض المصغر-ANGEM - غوفي, عبد الحميد; غقال, الياس (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
Micro enterprises have taken an important and essential role in the economic development strategies in most countries of the world. These enterprises represent a prominent part of the production sector in the different countries, whether developed or developing ones. Many economists believe that the development of such enterprises and the promotion of their creation, considered as the pillars of the process of economic and social development in both developed and developing countries. Since the early 1990s, micro enterprises have become the strongest alternative to many economies due to their characteristics as the increase of production capacity, the contribution to tackling the problems of poverty and unemployment ...etc.Financing these enterprises is one of the most important obstacles facing the owners, especially during the creation period, because of the reluctance of the financial institutions on the granting of credit for this kind ofenterprises.Algeria is one of the countries which interested in the development of micro-enterprises in past decade. the National Agency of management of micro-credit is one of the most important structures that aims at granting micro-credit to young people to create their own micro-enterprises besides covering the credit value granted by the commercial banks with a view to encourage these latter to grant credits to finance these kinds of enterprises